PENGARUH NISBAH TOTAL ETANOL – PKO DAN WAKTU REAKSI TERHADAP RENDEMEN DAN AKTIVITAS ANTIBAKTERI PRODUK ETANOLISIS MINYAK INTI SAWIT (PKO) - Mairisa Lestari; Murhadi Murhadi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2008)
The purposes of this work were to find the effects of ethanol-PKO ratio and reaction time on the yield and antibacterial activities of palm kernel oil ethanolysis products. The treatments were ratios of ethanolyisis mediums and duration of agitation. The medium treatments were ethanol 96% (NaOH 1%; w/w of oil) solution and PKO at ratio of 0,4; 0,7; 1,0; 1,3 and 1,6 (v/w) and the duration of agitation on a shaker at 300 rpm for 4, 6, 8, and 10 minutes. Antibacterial activities were tested using Staphylococcus aureus and Escherichia coli. The results showed ethanol-PKO ratio at 1,6 (v/w) effectively increased the yield of ethanolysis products for 4 up to 10 min, while the treatments at ratio of 0,4; 0,7; 1,0 (v/w) did not affect significantly, and at ratio of 1,3 (v/w) was optimum for 4 min. Ethanolysis products and their fractions for all treatments had antibacterial activities toward two bacteria (E. coli and S. aureus) with the average diameter of zone inhibition was 5,38 mm/15 mg. The optimum ethanol-PKO ratio and time of reaction were 1,3 (v/w) and 10 minutes to produce ethanolysis products, primarily for fraction 1 (uper layer after fractionation). Keywords: Antibacterial activities, ethanolysis, Palm Kernel Oil